(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The growing complexity and demand for energy in modern households have highlighted the need for intelligent and adaptive systems to manage and balance electrical loads efficiently. Unbalanced energy consumption can lead to frequent circuit overloads, increased electricity bills, reduced appliance lifespan, and safety hazards such as electrical fires. This paper presents the development of a mechatronic system designed specifically for dynamic load balancing in household environments. The system combines real-time sensing, microcontroller-based decision-making, and automated actuation to monitor energy usage and control the distribution of electrical loads across various devices. It uses a combination of current and voltage sensors, a central processing unit (such as Arduino or STM32), and relays to switch or redistribute loads based on priority and consumption thresholds. The system’s algorithm is capable of learning and adapting to usage patterns over time, offering both reactive and predictive load management. Experimental results indicate improved energy efficiency, reduced peak loads, and enhanced safety and stability of the household electrical system. The proposed solution also lays a foundation for integration into smart home environments and future smart grid technologies.